Digital Resources for Managing Wetlands: The Case of Playa Lake Research: A Preliminary Report: Methods - Bill Johnson; Marina Oliver (Issues in Science and Technology Librarianship, 1997)
The initial phase of this digital project has involved a collaborative approach to resource gathering. We have employed a diverse strategy of searching available bibliographic databases and current technologies to digitize relevant documents and images. The structure of this hypertext resource follows an intuitive menu whereby students, researchers, or managers may locate relevant articles or citations. Finally, we are considering several future enhancements to make this electronic collection of material on wetlands research more functional and more effective in meeting the information needs of interested parties into the next century.